Catalysts Leading to Sustainability: Multi-Stakeholder Collaborative Transformation in Poverty Alleviation in Kendari City - edy tadung; Alwi Alwi; Gita Susanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was investigates multi-stakeholder collaboration practices in the implementation of Regional Poverty Alleviation policies by the Kendari City Government in Southeast Sulawesi Province within the Regional Poverty Alleviation Coordination Team (TKPKD). The study aimed to formulate a multi-stakeholder collaboration framework through collaboration catalysts as factors for the success of sustainable collaborative practices. Materials and methods. We used a case study methodology to explore various types of data for this case study on TKPKD collaborative practices in Kendari City. Data were tabulated from more qualitative sources through analysis of in-depth interviews, documentaries, direct observations, and field visits. The in-depth interview framework was developed through detailed documentary analysis to achieve the goal of understanding collaborative practice events. Results The results indicate that collaboration catalysts in this study include jointly designed strategies, cooperative implementation, adaptive innovation, dialogic communication, contextual impacts, and shared values. Conclusions. The study concluded that implementing collaboration catalysts, defined as key characteristics or elements conceptualized as a framework within a series of interacting institutional conditions within the TKPKD, can lead to sustainable transformation in poverty alleviation.